The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1974
DOI: 10.1128/iai.10.1.128-135.1974
|View full text |Cite
|
Sign up to set email alerts
|

Elastase of Pseudomonas aeruginosa : Inactivation of Complement Components and Complement-Derived Chemotactic and Phagocytic Factors

Abstract: A purified elastase from Pseudomonas aeruginosa was highly destructive for fluid-phase and cell-bound Cl and C3 and fluid-phase C5, C8, and C9. Inactivation of C4, C2, C6, and C7 by the enzyme varied from 0 to 67%. Low concentrations of elastase generated, then inactivated, a chemotactic factor from human C5 but not from C3. Higher enzyme concentrations inactivated the C5 chemotactic activity at a faster rate. Elastase treatment of sensitized pseudomonads containing cell-bound C3 reduced the phagocytic indexes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(51 citation statements)
references
References 19 publications
2
49
0
Order By: Relevance
“…Similar characteristics for generation of chemotactic activity in serum, as we here describe for B. gingivalis, have previously been found for Streptoeoeeus pyogenes and Pseudomonas aeruginosa (15,19,29,30,31). Streptoeoeeus pyogenes has a surface bound C5a peptidase that specifically removes a six-aminoacid fragment from the C terminus of human C5a and abrogates the activity of the chemotaxin (15,30).…”
Section: Discussionsupporting
confidence: 82%
“…Similar characteristics for generation of chemotactic activity in serum, as we here describe for B. gingivalis, have previously been found for Streptoeoeeus pyogenes and Pseudomonas aeruginosa (15,19,29,30,31). Streptoeoeeus pyogenes has a surface bound C5a peptidase that specifically removes a six-aminoacid fragment from the C terminus of human C5a and abrogates the activity of the chemotaxin (15,30).…”
Section: Discussionsupporting
confidence: 82%
“…Following its purification and characterization by Morihara ef ai (1965), Pseudomonas elastase has been studied for both its proteolytic and elastolytic properties. Proteolytic effects of elastase include cleavage of immunoglobulln G proteins (Doring et ai, 1981), inactivation of alpha 1-proteinase inhibitor (Morihara ef ai, 1979), destruction of complement factors (Schultz and Miller, 1974), cleavage of human Received 6 August, 1991: revised 10 January, 1992accepted 16 January, 1991, 'Forcorrespondence, Tel, (614) 292 3761; Fax (614) 292 1538, type tl and IV collagens (Heck et ai. 1986b), and inactivation of human airway lysozyme (Jacquot ef ai.…”
Section: Introductionmentioning
confidence: 99%
“…A similar observation in a model of corneal infection with P aeruginosa in rats was obtained by Matsumoto et al (20). Further, it has also been reported that pseudomonal elastase destroys a wide range of substances of the host used for defense, such as immunoglobulin A (8), complement (28), and a plasma serine protease inhibitor (26), and that it suppresses neutrophil function (15).…”
Section: Discussionmentioning
confidence: 99%